Tutor profile: Rhianna A.
Solve the equation ln x +ln(x+2)= ln(x+6).
ln x + ln(x+2)= ln(x+6) ln (x(x+2))= ln(x+6) x(x+2)= x+6 x^2+2x= x+6 x^2+x-6=0 (x+3)(x-2)=0 x=-3 or x=2 Since x=-3 does not check in the original equation, x=2 is the only solution.
Subject: Basic Math
An apartment has 4 bedrooms. Each bedroom has 3 bookcases. How many bookcases are there in the apartment?
Using addition, you can argue that there are 12 bookcases in the apartment. ( 3 + 3 + 3 + 3 = 12) However, the problem can be solved faster by doing a multiplication of 3 and 4 since 3 × 4 = 12
Solve the equation 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13
Given the equation 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Multiply the factors. -15x - 10 - x + 3 = -16x - 20 +13 Group like terms. -16x - 7 = -16x - 7 Add 16x + 7 to both sides and write the equation as follows 0 = 0 The above statement is true for all values of x and therefore all real numbers are solutions to the given equation.
needs and Rhianna will reply soon.